Possible Structural Implications of 20 Mutations in the Protein C Protease Domain - Greengard, Judith S; Griffin, John H; Fisher, Cindy L (Thrombosis and Haemostasis, 1994)
Analysis of naturally occurring protein mutations yields valuable insights into functionally important sequences. Characterizing mutations responsible for protein C deficiency at the molecular level has been the subject of intensive investigation. In a previous study, a three-dimensional model of the serine protease domain of protein C was used to analyze the set of protease domain mutations previously available. The mutations were largely found to fall into a limited number of categories. A recently updated protein C mutation data base has provided a number of new mutations which have been analyzed for structural predictions.